Analisis Kemudahan Pembayaran, Tingkat Resiko dan Trust terhadap Keputusan Pembelian Menggunakan Fitur Shopee PayLater: Studi Kasus Pengguna Shopee Masyarakat Surakarta - Oktavia, Yasmin; Istiatin; Sarsono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this study is to investigate how the convenience of payment impacts buying choices when utilizing the Shopee PayLater option, to assess how the level of risk influences purchasing decisions with the Shopee PayLater feature, and to examine the impact of trust on buying decisions facilitated by the Shopee PayLater functionality. Shopee users in Surakarta, Central Java, were studied. This research approach employs a quantitative research design. all customers who have and have used Shopee PayLater in the Surakarta district of Central Java. The sample size for this study is 100 people. Purposive sampling is used in the sampling procedure. Data is gathered through the utilization of a survey, and the analysis involves employing traditional assumption testing, multiple linear regression, t-tests, and the determination coefficient test. The results reveal that the convenience of payment has a noteworthy and positive impact on buying choices carried out using the Shopee PayLater option. Similarly, the degree of risk exhibits a significant and favorable influence on purchasing decisions made through the Shopee PayLater feature. Furthermore, trust also demonstrates a substantial and beneficial effect on purchasing decisions facilitated by the Shopee PayLater functionality. The findings of multiple linear regression analysis show that Trust is the most important variable.